Flagship entry in online marketplaces - Ginger Zhe Jin; Zhentong Lu; Xiaolu Zhou; Lu Fang (Bank of Canada, 2023)
In this paper, we empirically study how flagship entry in an online marketplace affects consumers, the platform, and various sellers on the platform. We find flagship entry may benefit consumers by expanding the choice set, by intensifying price competition within the entry brand, and by improving consumer perception for parts of the platform. In the meantime, flagship entry cannibalizes the sales of same-brand sellers, while other brands may gain as the buyer base expands on the platform. Counterfactual simulation suggests that flagship entry improves the gross merchandise value of the platform and overall consumer welfare in most cases.
Keywords: D4; L1; L8; 330; Market structure and pricing; Economic models